HOW TO SEARCH THE PLACE BRAND IDENTITY DISTINGUISHED FEATURES? THE LOCAL STAKEHOLDERS' PERSPECTIVE - Ewa Glińska (Polityki Europejskie, Finanse i Marketing)
Shaping a recognizable image/brand of a particular town/city has become one of the possibilities to achieve the competitive advantage on the contemporary territory market. The main purpose of the paper is to present the categories of place brand identity distinguishing features identified by local stakeholders. The results of the research includes suggestions how to select attributes of urban identity in relation to image management especially in small towns. The research method used in developing this paper was focus group interviews (FGIs) carried out in the period July 2011 - June 2012 in nine towns in Podlaskie region in Poland. The FGIs’ participants were moderated towards identifying their towns’ identity distinguishing features which seem most attractive from the marketing point of view and could potentially be used by local authorities in the process of place branding. Statements of the participants interviewed have identified two groups of the distinguishing characteristics of the specific nature of the analyzed towns: the emotional attributes and functional attributes. In the first category such as distinguishing characteristics of the town are located like: the atmosphere, the history and local culture, and human potential. The other category consists of: technical facilities, social investment, as well as the strategic location and the products of local companies.